Defense perspectives in international criminal justice / Colleen Rohan, Gentian Zyberi - Rohan, Colleen M.; Zyberi, Gentian (Cambridge University Press, 2017)
This examination of the role of the defense in international criminal proceedings highlights its contribution to the development of international criminal law and the fair administration of international criminal justice. Written by leading international practitioners and scholars, it combines the practice and theory of international criminal law in order to provide a first-hand perspective on the significant challenges involved in the administration of international criminal justice. The authors examine, among other issues, the role of the defense during the different stages of international criminal proceedings, the key aspects of defense work which seek to ensure the accused's right to a fair trial, professional ethics, the United Nations Residual Mechanism for International Tribunals, and post-conviction remedies and issues relating to those serving prison sentences.